2003
DOI: 10.1097/01.mbc.0000061293.28953.8c
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and endothelial cell dysfunction in sickle cell disease is unrelated to reduced antioxidant capacity

Abstract: Possible pathogenetic processes in sickle cell disease include antioxidants, endothelial and platelet changes, and hypercoagulability. Hypothesizing relationships between these processes, we recruited 47 young adult patients (mean age 19 years) with homozygous sickle cell disease and 40 age-, race- and sex-matched healthy controls and measured plasma markers representative of these processes. We found raised plasma von Willebrand factor (P = 0.001) and intercellular adhesion molecule (P = 0.016, both marking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
8
19
0
Order By: Relevance
“…Mitochondrial dysfunction is associated with platelet activation and hemolysis SCD patients exhibit augmented platelet activation compared with healthy subjects. [13][14][15] This phenomenon was corroborated in our cohort in which SCD patient platelets showed a significantly greater percentage of activated platelets (21 6 6.9%; n 5 24) than controls (11.0 6 2.3%, n 5 19, P 5 .029; Table 1). Thus, we next sought to determine whether the bioenergetic dysfunction identified in SCD platelets was associated with aberrant platelet activation.…”
Section: Scd Patient Platelets Have Altered Bioenergeticssupporting
confidence: 70%
See 3 more Smart Citations
“…Mitochondrial dysfunction is associated with platelet activation and hemolysis SCD patients exhibit augmented platelet activation compared with healthy subjects. [13][14][15] This phenomenon was corroborated in our cohort in which SCD patient platelets showed a significantly greater percentage of activated platelets (21 6 6.9%; n 5 24) than controls (11.0 6 2.3%, n 5 19, P 5 .029; Table 1). Thus, we next sought to determine whether the bioenergetic dysfunction identified in SCD platelets was associated with aberrant platelet activation.…”
Section: Scd Patient Platelets Have Altered Bioenergeticssupporting
confidence: 70%
“…In addition to overt thrombus formation, activated platelets contribute to both acute and chronic vasculopathy in SCD patients through the secretion of soluble vasoactive and mitogenic factors, promoting vascular damage, red cell adhesion to the endothelium, and intimal hyperplasia. 13,14,[17][18][19] Consistent with this, augmented platelet activation observed basally in steady-state SCD patients is further elevated during acute vasoocclusive crisis and correlates with the severity of PAH, a chronic vascular proliferative complication and leading cause of mortality in adult SCD patients. [14][15][16][30][31][32] Although patients in vaso-occlusive For personal use only.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Intriguingly, some studies have suggested that cytoreductive therapy may not reverse all abnormal markers of platelet, coagulation pathway and endothelial activation; specifically plasma fibrinogen, Pselectin, von Willebrand factor and soluble vascular cell adhesion molecule (sVCAM). 17 Currently, the pathogenesis of platelet activation in MPD is unknown, although a large proportion of patients have a deficiency of lipoxygenase, which could increase availability of endoperoxides to produce thromboxane A2. 18 The same patients however have tendency to a hemorrhagic rather than thrombotic diathesis.…”
Section: Platelet Activationmentioning
confidence: 99%